2015
DOI: 10.1016/j.ijrobp.2015.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Local Recurrence After Rituximab-Based Chemotherapy Alone in Stage III and IV Diffuse Large B-Cell Lymphoma: Guiding Decisions for Consolidative Radiation

Abstract: Purpose The role of consolidative radiotherapy (RT) for stage III and IV DLBCL in the era of rituximab is not well defined. There is evidence that some patients with bulky disease may benefit, but patient selection criteria are not well established. We sought to identify a subset of patients who experienced a high local failure rate after receiving rituximab-based chemotherapy alone and hence may benefit from the addition of consolidative RT. Methods and Materials 211 stage III and IV DLBCL patients treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
3
24
0
Order By: Relevance
“…Furthermore, prior studies have reported an association of bulky disease with worse outcomes for DLBCL patients [43]. In a previous study of 89 patients treated for DLBCL after primary immunochemotherapy, those with bulky disease (defined as > 5 cm) were approximately 7 times more likely to recur locally than those with smaller initial disease [44]. In our chemo-sensitive cohort, all patients had bulky disease at time of diagnosis (median 11.9 cm).…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, prior studies have reported an association of bulky disease with worse outcomes for DLBCL patients [43]. In a previous study of 89 patients treated for DLBCL after primary immunochemotherapy, those with bulky disease (defined as > 5 cm) were approximately 7 times more likely to recur locally than those with smaller initial disease [44]. In our chemo-sensitive cohort, all patients had bulky disease at time of diagnosis (median 11.9 cm).…”
Section: Discussionmentioning
confidence: 77%
“…Prognostic factors that were included were: presence of B-symptoms, bone marrow involvement, LDH level, bulky disease as defined by greater than 5 cm per institutional practice,[20] IPI score, and the number of extranodal sites. Patients were followed with periodic physical exams and imaging.…”
Section: Methodsmentioning
confidence: 99%
“…The current standard first‐line management for patients with aggressive B‐cell non‐Hodgkin lymphoma (NHL) is R‐CHOP (Rituximab, Cyclophosphamide, Doxorubicin, Vincristine, Prednisone) chemotherapy . Indications for consolidation radiotherapy after first‐line chemotherapy include bulky or skeletal disease on initial scans at diagnosis or residual disease on imaging post‐chemotherapy . These recommendations were based on anatomical imaging and before the widespread use of positron emission tomography (PET).…”
Section: Introductionmentioning
confidence: 99%
“…1 Indications for consolidation radiotherapy after first-line chemotherapy include bulky or skeletal disease on initial scans at diagnosis or residual disease on imaging postchemotherapy. [2][3][4][5][6] These recommendations were based on anatomical imaging and before the widespread use of positron emission tomography (PET). PET, using 18 F-Fluorodeoxyglucose (FDG), is now the standard tool for assessing response to treatment, having been shown to be more accurate at defining residual and recurrent lymphoma and a better predictor of relapse than anatomical imaging.…”
Section: Introductionmentioning
confidence: 99%